Unsupervised learning for identifying events in active target experiments - Solli, R.; Bazin, D.; Hjorth-Jensen, M.; Kuchera, M.P.; Strauss, R.R. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2021)
This article presents novel applications of unsupervised machine learning methods to the problem of event separation in an active target detector, the Active-Target Time Projection Chamber (AT-TPC) (Bradt, 2017). The overarching goal is to group similar events in the early stages of the data analysis, thereby improving efficiency by limiting the computationally expensive processing of unnecessary events. The application of unsupervised clustering algorithms to the analysis of two-dimensional projections of particle tracks from a resonant proton scattering experiment on 46Ar is introduced. We explore the performance of autoencoder neural networks and a pre-trained VGG16 (Simonyan and Zisserman, 2015) convolutional neural network. We study clustering performance on both data from a simulated  46Ar experiment, and real events from the AT-TPC detector. We find that a k-means algorithm applied to simulated data in the VGG16 latent space forms almost perfect clusters. Additionally, the VGG16+k-means approach finds high purity clusters of proton events for real experimental data. We also explore the application of clustering the latent space of autoencoder neural networks for event separation. While these networks show strong performance, they suffer from high variability in their results.